2016
DOI: 10.7554/elife.12850
|View full text |Cite
|
Sign up to set email alerts
|

Wnt, Ptk7, and FGFRL expression gradients control trunk positional identity in planarian regeneration

Abstract: Mechanisms enabling positional identity re-establishment are likely critical for tissue regeneration. Planarians use Wnt/beta-catenin signaling to polarize the termini of their anteroposterior axis, but little is known about how regeneration signaling restores regionalization along body or organ axes. We identify three genes expressed constitutively in overlapping body-wide transcriptional gradients that control trunk-tail positional identity in regeneration. ptk7 encodes a trunk-expressed kinase-dead Wnt co-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 51 publications
4
93
0
Order By: Relevance
“…This observation supports the hypothesis that the wnt1 ligand, secreted by the newly formed posterior organizer, is the morphogen that sustains nuclear translocation of β-CATENIN-1 at the posterior pole during regeneration (Adell et al, 2009;Petersen and Reddien, 2009b). Later on, the nested expression of the other posterior Wnt ligands would control the re-establishment and maintenance of the gradient (Hayashi et al, 2011;Lander and Petersen, 2016;März et al, 2013;Scimone et al, 2016;Sureda-Gómez et al, 2015) (Fig. 6A).…”
Section: A Gradient Of β-Catenin-1 Along the Ap Axissupporting
confidence: 78%
See 2 more Smart Citations
“…This observation supports the hypothesis that the wnt1 ligand, secreted by the newly formed posterior organizer, is the morphogen that sustains nuclear translocation of β-CATENIN-1 at the posterior pole during regeneration (Adell et al, 2009;Petersen and Reddien, 2009b). Later on, the nested expression of the other posterior Wnt ligands would control the re-establishment and maintenance of the gradient (Hayashi et al, 2011;Lander and Petersen, 2016;März et al, 2013;Scimone et al, 2016;Sureda-Gómez et al, 2015) (Fig. 6A).…”
Section: A Gradient Of β-Catenin-1 Along the Ap Axissupporting
confidence: 78%
“…In recent years, functional characterization of the key elements of the canonical Wnt pathway suggested that the morphogenetic role of the wnt ligands secreted by a posterior organizing center could generate a gradient of nuclear β-CATENIN-1 responsible for the specification and maintenance of the planarian AP axis (Adell et al, 2009 and Reddien, 2009b;Scimone et al, 2016;Sureda-Gómez et al, 2015). The nested expression of several Wnt ligands (wnt1, wnt11-1, wnt11-2 and wnt11-5) in the pharyngeal and tail region of the planarian body, and the expression of Wnt inhibitors (notum and sFRP) in the anterior tip of the head gave support to the gradient hypothesis Gurley et al, 2010;Lander and Petersen, 2016;Petersen and Reddien, 2011;Scimone et al, 2016;Sureda-Gómez et al, 2015). Additionally, inhibition of these posterior Wnt ligands leads to 'tail-less' or 'two-headed' planarians, as does the inhibition of β-catenin-1 itself (Adell et al, 2009;Gurley et al, 2010;Petersen and Reddien, 2009b;Sureda-Gómez et al, 2015).…”
Section: A Gradient Of β-Catenin-1 Along the Ap Axismentioning
confidence: 84%
See 1 more Smart Citation
“…Inhibition of multiple PCGs (such as bmp4, wntP-2 , and ndl-3 ) by RNA interference (RNAi) causes patterning phenotypes, such as ectopic heads, pharynges, or eyes (2326). After amputation, PCG expression domains are rapidly re-established in muscle (in a matter of 2–3 days).…”
Section: Transient Discordance Between Anatomy and Positional Informamentioning
confidence: 99%
“…Colorimetric (NBT/BCIP) or fluorescence in situ hybridizations were performed as described (Lander and Petersen, 2016) after fixation in 4% formaldehyde and bleaching (Pearson et al, 2009) using blocking solution containing 10% horse serum and western blot blocking reagent (Roche) (King and Newmark, 2013). Digoxigenin-or fluorescein-labeled riboprobes were synthesized as described (Pearson et al, 2009) For immunostainings, animals were fixed in Carnoy's solution as described (Hill and Petersen, 2015), using tyramide amplification to detect labeling with rabbit anti-phospho-ser10 Histone H3 (1:3000, Cell Signaling D2C8, lot 3377S) or Alexa Fluor 586-conjugated goat anti-mouse IgG (Invitrogen A11031, lot 822389) to detect labeling with mouse antisynapsin (1:50, anti-SYNORF1, Developmental Studies Hybridoma Bank clone 3C11).…”
Section: In Situ Hybridization and Immunostainingmentioning
confidence: 99%